Burden or benefit? Regulation as a dynamic influence on small business performance. (March 2015) - Kitching, John; Hart, Mark; Wilson, Nick
This article contributes to contemporary debates concerning the impact of regulation on small business performance. Reassessing previous studies, we build our insights on their useful, but partial, approaches. Prior studies treat regulation principally as a static and negative influence, thereby neglecting the full range of regulatory effects on business performance. This study adopts a more nuanced approach, one informed by critical realism, that conceptualises social reality as stratified, and social causality in terms of the actions of human agents situated within particular social-structural contexts. We theorise regulation as a dynamic force, enabling as well as constraining performance, generating contradictory performance effects. Such regulatory effects flow directly from adaptations to regulation, and indirectly via relationships with the wide range of close and distant stakeholders with whom small businesses interact. Future research should examine these contradictory regulatory influences on small business performance.